If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -8g = 10 + g Solving 4 + -8g = 10 + g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. 4 + -8g + -1g = 10 + g + -1g Combine like terms: -8g + -1g = -9g 4 + -9g = 10 + g + -1g Combine like terms: g + -1g = 0 4 + -9g = 10 + 0 4 + -9g = 10 Add '-4' to each side of the equation. 4 + -4 + -9g = 10 + -4 Combine like terms: 4 + -4 = 0 0 + -9g = 10 + -4 -9g = 10 + -4 Combine like terms: 10 + -4 = 6 -9g = 6 Divide each side by '-9'. g = -0.6666666667 Simplifying g = -0.6666666667
| 5(x-16)=x-20 | | 2x^2-1=120 | | -3d+7=-9 | | 3/2x-4=12 | | -49+2x=23 | | ln(2y)=x | | 2x(y)=76 | | -8=3(k-7) | | 4+13=5 | | 2x+y=76+y | | g+242=79 | | 6x+4(-7x+6)=-130 | | a-4a=3a+1 | | -3.1x-7=-2.2x+2 | | 5000=2x+300 | | 2x(x-y)= | | 14x-65=73+17x | | 28.96+b=57.39 | | -419+6x=-9x+196 | | 57=2h | | 9=w-35 | | (2x-7)(-4x+18)=-24x+100 | | (9x+2)+(7x+2)=180 | | 7r^2-14r-31=-10 | | .75h+3=6(-h+3) | | 4.9x^2+6x-650=0 | | w-15=31/2 | | 18x+12=62-7x | | 7r*2-14r-31=-10 | | -.86x+11=-43 | | 5x+2x+3x=20 | | 420•5/6 |